(untitled) (Bangladesh Journal of Urology, 2020)
Objective: The aim of the study was to compare the endoscopic versus percutaneous approach (blind) to control the obturator jerk in patients undergoing transurethral resection of bladder tumors under spinal anesthesia. Materials and methods: A prospective observational study was performed in Department of Urology, Chittagong Medical College, Chittagong and some Private Hospitals (Ltd.) in Chittagong city during the period from January 2016 to June 2016. Total 100 patients were grouped into two, on alternate basis. Fifty(50) patients in group- A conducted with endoscopic infiltration with 20ml of injection 2% lignocaine at the bladder tumor base and another 50 patients in group-B, conducted with blind percutaneous technique with same drug and volume ( 20ml inj.2% lignocaine) to control obturator jerk. Severity of obturator jerk in both procedure, percentage of complete resection, ONB procedure related time, ONB procedure related complications and surgeon’s satisfaction level were recorded and compared between two approaches. Chi-square analysis was performed to compare the ease of approach and outcome of the two techniques. A value of P<0.05 was considered statistically significant. Results: The mean age of the patients were 59.44+7.681. In group-A, 50 patients were given inj. 2% lignocaine endoscopically at the bladder tumor base to control obturator jerk. Twenty five patients (50%) had no jerk, 20 patients(40%) developed mild jerk and 5 patients (10%) developed moderate jerk and no patients developed severe jerk. Second attempt was taken in moderate jerk patients (5 patients) and succeeded in 3(6%) patients. So, in this group, complete resection of bladder tumor was possible in 96%. In group B, complete resection of bladder tumor was possible in 84%. Statistical analysis was done and result is significant in case of endoscopic procedure to control obturator jerk(p<0.05). ONB Procedure related time was <20 mins. in 32(64%) patients in group-A and 45 (90%) patients in group- B. 20 mins. or more time was required for 18 (36%) patients in group-A and 5 (10%) patients in group-B. Statistical analysis was done and result is significant in percutaneous (blind) technique (p<0.05). ONB procedure related complications in group-A and Group –B were noted. Statistical analysis was done and result is insignificant (p>0.05). Surgeons satisfaction level were recorded on the basis of obturator jerk block and complete resection and which was statistically significant in favour of endoscopy group (p<0.05). Conclusion: It is concluded that endoscopic injection of 2% lignocaine into the bladder tumor base is better in case of jerk elimination and complete resection than blind percutaneous approach. Though, ONB procedure related time was significantly less in percutaneous group. Bangladesh Journal of Urology, Vol. 21, No. 2, July 2018 p.120-126